Traumatic spinal cord injury: current concepts and treatment update - Carolina Rouanet; Danyelle Reges; Eva Rocha; Vivian Gagliardi; Gisele Sampaio Silva (Arquivos de Neuro-Psiquiatria)
ABSTRACT Spinal cord injury (SCI) affects 1.3 million North Americans, with more than half occurring after trauma. In Brazil, few studies have evaluated the epidemiology of SCI with an estimated incidence of 16 to 26 per million per year. The final extent of the spinal cord damage results from primary and secondary mechanisms that start at the moment of the injury and go on for days, and even weeks, after the event. There is convincing evidence that hypotension contributes to secondary injury after acute SCI. Surgical decompression aims at relieving mechanical pressure on the microvascular circulation, therefore reducing hypoxia and ischemia. The role of methylprednisolone as a therapeutic option is still a matter of debate, however most guidelines do not recommend its regular use. Neuroprotective therapies aiming to reduce further injury have been studied and many others are underway. Neuroregenerative therapies are being extensively investigated, with cell based therapy being very promising.